Microstructural and structural stability of rapidly solidified gold-titanium alloys. - Van Heerden, David Peter (Centre for Materials Engineering, 2024)
An investigation has been carried out into the effect of rapid solidification on the microstructure and structural order present in dilute Au-Ti alloys, and the subsequent evolution of these properties on post-solidification heat treatment. Alloys of compositions lwt.% Ti, 2wt.% Ti, 3wt.% Ti and 5wt.% Ti have been rapidly solidified by a technique known as chill block melt spinning (CBMS). The microstructure and structural order present in the alloys both directly on solidification and after post- solidification heat treatment have been characterised using optical microscopy, scanning electron microscopy and transmission electron microscopy; the evolution of the mechanical properties on post-solidification heat treatment has been determined by means of microhardness tests. The flow characteristics of the molten alloys are observed to deteriorate with increasing Ti content resulting in an increase the cooling rate experienced by the alloys during rapid solidification with increasing solute concentration. The as-solidified alloy microstructures are therefore rationalised on the basis of variations in both cooling rate during CBMS and solute content. TEM examination of the as-solidified ribbons demonstrates that alloys containing up to 3wt.% Ti exhibit little evidence of either solute segregation or the formation of the equilibrium, long-range-ordered (Dla) Au₄Ti phase. In a 5wt.% Ti alloy the (Dla) Au4Ti phase is observed to nucleate during processmg. Long-exposure electron diffraction patterns from 2wt.% Ti, 3wt.% Ti and 5wt.% Ti alloys reveal diffuse intensity maxima consistent with the presence of <1½0> special-point order, a state of order which has not been identified previously in Au-Ti alloys. On the basis of electron diffraction patterns taken from these alloys the incorporation of elements of both DO₂₂ and Dla structures within the lattice is appropriate in the description of the structural order giving rise to special-point reflections. The state of order present in the as-solidified 2wt.% Ti and 3wt.% Ti alloys is shown to be best described by incorporating both elements of <1½0> special-point order and elements of the (D1a) long-range-ordered structure. In addition, the nature and distribution of the three-dimensional diffuse streaking observed in zone-axis patterns from a variety of different orientations is discussed and interpreted. This state of order is observed to be stable up to a temperature of 335°C. The lwt.% Ti alloy contained only 0.65wt.% Ti after processing. This loss of Ti results in extensive grain growth on heat treatment at temperatures above 350°C with no detectable second phase formation; as a result the alloy microhardness decreases on heat treatment. In the 2wt.% Ti and 3wt.% Ti alloys no grain growth is observed to occur on heat treatment at temperatures of up to S00°C. On heat treatment at 350°C the Au₄Ti phase is shown to precipitate in these alloys with a commensurate increase in the alloy microhardness. However, extended heat treatment at 500°C results in the coarsening of the Au₄Ti precipitates and is associated, in some instances, with a loss of precipitate coherency and an annealing out of orientational variants of the Au₄Ti phase.